2018
DOI: 10.4034/pboci.2018.181.65
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Anxiety and Associated Factors among Indian Children

Abstract: Objective: To determine the prevalence of dental anxiety and associated factors among 5 to10 years old Indian children. Material and Methods: In this cross-sectional study, the sample was composed by 462 children (240 male and 222 female).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…6 The prevalence of anxiety to dental treatment is reported to be 24.5% among 5-10-year-old Indian children. 7 It was noticed that 57.2% of children exhibit anxiety before the start of dental procedures and 46.2% of children were anxious during the procedures. 8 The increase in preoperative anxiety makes the child uncooperative and poses a difficulty in performing dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 The prevalence of anxiety to dental treatment is reported to be 24.5% among 5-10-year-old Indian children. 7 It was noticed that 57.2% of children exhibit anxiety before the start of dental procedures and 46.2% of children were anxious during the procedures. 8 The increase in preoperative anxiety makes the child uncooperative and poses a difficulty in performing dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Groups with lower socioeconomic standards have also exhibited a higher prevalence of dental anxiety and behaviour management problems. 20 It is possible that these differences can be levelled out in countries where organised free dental care for children is provided. Hence, some studies from Sweden and Norway have failed to establish a relationship between socioeconomic variables and dental fear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed multiple etiological factors related to negative child’s behavior and anxiety in the dental clinics such as cultural background, parental anxiety, pain and discomfort, age, sociodemographic factors, and genetic and previous dental or sibling experience [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%